THE PARADOXES OF ECONOMIC DEVELOPMENT OF KENYA (Вісник: Міжнародні відносини, 2024)
East Africa is one of critically important regions located at the crossroads of trade routes of the Indian Ocean and endowed with considerable reservoirs of drinking water within the net of the Great Lakes, while it is known at the same time for the Great Rift Valley with geothermal potential and for volcanic national soils whose productivity is defined by Equatorial weather. The article is devoted to the research of the peculiarities of economic development of Kenya that is considered an important regional rival of Tanzania in logistic and touristic respects.
Keywords: Kenya, Tanzania, Somalia, ports, airports, highways, tourism, export, remittances, refugees